Academic Supervision As One Of The Education Policy Implementations (Case Study of the Islamic Religious Education Teacher Working Group in Sungai Tabuk District, Banjar Regency in the Perspective of General Education) - Soro, Suharyanto H; Handayani, Sri; Maki, Akhmad; Khalifaturrahmah, Khalifaturrahmah (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Academic supervision is closely related to the quality of learning. How to increse the quality of learning is the poblem in education world. In the simple way, a quality of learning process requires a professional teacher. Education policy is a public policy that regulates specifically related to the absorption of resources, allocation and distribution of resources as well as regulation of behavior in the realm of education. The purpose of this research is to find out whether academic supervision can improve teacher professionalism and identify factors that can increase the professional understanding of Islamic Religious Education teachers at SD Banjar Regency, South Kalimantan. Researchers used the method of observation, interviews, and documentation to obtain research data. The sample selection was carried out by purposive sampling, namely five teachers with masters degrees. Researchers used in-depth interviews with the aim of gathering information according to the research objectives. The results of the research findings indicated that the implementation of academic supervision as one of the policies in the world of education can increase the professionalism of Islamic Religious Education teachers. This is closely related to the quality of learning carried out by the teacher. Planning well, being objective and factual are factors that can increase teacher enthusiasm and self-confidence.Â